2022
DOI: 10.1111/inm.13079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of strengths model training and supervision on the therapeutic practice of Australian mental health clinicians

Abstract: This study explored the impact of Strengths Model training, supervision and mentorship on the practice of a group of multi-disciplinary mental health clinicians that included mental health nurses, social workers, psychologists, and occupational therapists. A qualitative approach that combined critical realism and grounded theory was used. The findings demonstrated how a substantive category, Getting to Know Clients Better, facilitated participants' progression through a basic social psychological process, Beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…SMCM generated a more positive view from the case manager that consumers noticed in this study. This was also described in research by Pullman et al (2023) as the client becoming visible to the case manager, supporting them to see the whole person of the consumer, and to have a greater understanding of the life of the consumer and to be more empathetic towards the consumer. In this study, consumers reported that this new, holistic and strengths focused view that case managers now had of them because of SMCM created an improved relationship.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…SMCM generated a more positive view from the case manager that consumers noticed in this study. This was also described in research by Pullman et al (2023) as the client becoming visible to the case manager, supporting them to see the whole person of the consumer, and to have a greater understanding of the life of the consumer and to be more empathetic towards the consumer. In this study, consumers reported that this new, holistic and strengths focused view that case managers now had of them because of SMCM created an improved relationship.…”
Section: Discussionmentioning
confidence: 95%
“…A study by Roebuck, Latimer, et al (2022) found that high‐fidelity SMCM was associated with a stronger working relationship between case managers and consumers, and that this in turn positively influenced consumer hope, community functioning and quality of life. SMCM has also been found to reinvigorate practice and reduce levels of emotional exhaustion for clinicians (Chopra et al, 2009; Deane et al, 2019; Petrakis et al, 2013; Pullman et al, 2023; Tsoi et al, 2019). More recently, SMCM has been found to improve recovery‐orientated practice in an Australian context (Pullman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong structure of recovery‐focussed mentoring and supervision would assist therapists to build the confidence and capacity to embrace positive risk‐taking and support greater self‐determination (Pullman et al, 2023). Participants in this study emphasised the importance of working on themselves by engaging in critical self‐reflection and self‐development.…”
Section: Discussionmentioning
confidence: 99%